Constructal design applied to the light resin transfer molding (LRTM) manufacturing process - Isoldi, Liércio André (2013)
The Light Resin Transfer Molding (LRTM) is a manufacturing process where a closed mold pre-loaded with a porous fibrous preform is filled by a liquid resin injected through an empty channel (without porous medium) which runs all around the perimeter of the mold, producing polymeric composite parts. Using the capability of FLUENT® package to simulate a multiphase flow (resin and air) in a geometry composed by porous media regions and empty regions, a computational model based on the Finite Volume Method (FVM) was applied to reproduce the resin flow behavior during the LRTM process. The aim of this work was to define the optimal geometry for the empty channel (border) by means the Constructal Design method. To do so, considering a border with a rectangular cross sectional area, the degree of freedom wb/tb (ratio between the width and thickness of the border) can vary while the border volume is kept constant. The results showed that employing the Constructal Design it is possible to decrease the filling time of the LRTM process in almost 20 %, being this an unpublished use for the Constructal Theory.